Composite solid-state electrolyte based on needleless electrospinning technology and preparation method thereof
Patent Information
- Application Number
- CN202611259146.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]现有复合固态电解质的制备方法多为简单的共混浇铸法,无机填料在聚合物基体中易发生团聚,难以形成连续的离子传输网络,导致其离子电导率提升有限;并且,传统方法制备的电解质膜机械强度不足,难以有效抑制锂枝晶的生长
(1)本发明通过无针静电纺丝技术,将高离子电导率的无机纳米填料均匀地固定在复合纤维骨架中,形成连续的三维离子传输通道,避免了无机纳米填料的团聚,大幅提升了复合固态电解质的离子电导率,其复合固态电解质在25℃下的离子电导率可达1×10-4S/cm以上。
Smart Images

Figure CN123018096A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid electrolyte technology, specifically relating to a composite solid electrolyte based on needleless electrospinning technology and its preparation method. Background Technology
[0002] With the rapid development of electric vehicles, portable electronic devices, and personal intelligence, the demand for high-energy-density and high-safety lithium-ion batteries is becoming increasingly urgent. Traditional lithium-ion batteries use organic liquid electrolytes, which pose safety hazards such as flammability and leakage, severely limiting their application in high-energy-density systems. Solid-state electrolytes, due to their advantages such as non-flammability, no leakage, wide electrochemical window, and excellent mechanical strength, are considered a key approach to solving these problems.
[0003] Solid electrolytes are mainly classified into inorganic solid electrolytes, polymer solid electrolytes, and organic-inorganic composite solid electrolytes. Inorganic solid electrolytes, such as lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanium oxide (LLTO), and titanium dioxide (TiO2), have extremely high ionic conductivity (up to 10). -3 While polymeric solid electrolytes (PSI) exhibit good flexibility and interfacial contact, they also have high rigidity, poor electrode interface contact, and poor processability. Polymer solid electrolytes such as polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), and polyethylene oxide (PEO) possess good flexibility and interfacial contact, but their room temperature ionic conductivity is low (typically <10 S / cm). -5 (S / cm). Therefore, combining inorganic fillers with polymer matrices to prepare composite solid electrolytes with both high ionic conductivity and good flexibility has become a research hotspot.
[0004] Existing methods for preparing composite solid electrolytes are mostly simple blending and casting methods. Inorganic fillers tend to agglomerate in the polymer matrix, making it difficult to form a continuous ion transport network, resulting in limited improvement in ionic conductivity. Furthermore, electrolyte membranes prepared by traditional methods have insufficient mechanical strength, making it difficult to effectively suppress the growth of lithium dendrites. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing composite solid electrolytes based on needle-free electrospinning technology, which can at least solve some of the defects existing in the prior art.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: The preparation method of composite solid electrolyte based on needle-free electrospinning technology includes the following steps: S1. Dissolve the inorganic nanofiller and polymer matrix in a solvent and stir until homogeneous to obtain a spinning precursor solution; S2. The spinning precursor liquid is spun using a needleless electrospinning device, and a composite fiber skeleton with a three-dimensional network structure is collected. S3. Provide a polymer precursor solution, the polymer precursor solution comprising a polymer monomer, a crosslinking agent, an additive, and a lithium salt; S4. Add a thermal initiator to the polymer precursor solution, and immerse the composite fiber skeleton in the mixed solution of the polymer precursor solution and the thermal initiator. Under heating conditions, the impregnated composite fiber skeleton undergoes an in-situ polymerization reaction, and after curing, a composite solid electrolyte is obtained.
[0007] Furthermore, in S1, the inorganic nanofiller has a mass percentage of 3-8% in the spinning precursor solution, and the polymer matrix has a mass percentage of 8-12% in the spinning precursor solution.
[0008] Furthermore, in S1, the inorganic nanofiller is at least one of lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, and titanium dioxide; the polymer matrix is at least one of polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polymethyl methacrylate, polyvinyl alcohol, and polyimide; and the solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, deionized water, or ethanol.
[0009] Furthermore, in S2, the process parameters of the needleless electrospinning equipment are: spinning voltage of 30-80kV, receiving distance of 150-250mm, spinning ambient temperature of 20-40℃, and relative humidity of 30-50%.
[0010] Furthermore, in S3, the mass ratio of the polymer monomer, crosslinking agent, and additive is (2-5):(1-3):(0.5-1.5), and the lithium salt concentration is 1-3M.
[0011] Furthermore, in S3, the polymerizing monomer is at least one of 2,2,3,4,4,4-hexafluorobutyl methacrylate, succinic anion, methyl methacrylate, acrylonitrile, and 1,3-dioxolane; the crosslinking agent is at least one of polyethylene glycol diacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, and polyethylene glycol dimethacrylate; the additive is at least one of vinylene carbonate, fluoroethylene carbonate, lithium difluorooxalate borate, and succinic anion; and the lithium salt is at least one of LiTFSI, LiFSI, LiFTFSI, LiPTFSI, LiDFOB, LiPF6, and LiBF4.
[0012] Furthermore, the method for preparing the mixed solution of the polymer precursor solution and the thermal initiator includes: The polymer monomer, crosslinking agent, first-part lithium salt and thermal initiator are mixed to obtain component A; The additive and the second lithium salt were mixed to obtain component B; The mixture of component A and component B yields a mixed solution.
[0013] Furthermore, in S4, the thermal initiator is azobisisobutyronitrile; the heating temperature for the in-situ polymerization reaction is 50–80°C, and the reaction time is 1–4 h.
[0014] In addition, the present invention also provides a composite solid electrolyte, which is prepared by the above-described method for preparing composite solid electrolyte. The composite solid electrolyte includes a composite fiber skeleton with a three-dimensional network structure and an in-situ polymer matrix filled in the pores of the composite fiber skeleton.
[0015] Furthermore, the thickness of the composite solid electrolyte is 20–60 µm, and the ionic conductivity of the composite solid electrolyte at 25 °C is 1 × 10⁻⁶. -4 S / cm or higher.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses needle-free electrospinning technology to uniformly fix inorganic nanofillers with high ionic conductivity into the composite fiber skeleton, forming a continuous three-dimensional ion transport channel. This avoids the aggregation of inorganic nanofillers and significantly improves the ionic conductivity of the composite solid electrolyte. The ionic conductivity of the composite solid electrolyte at 25℃ can reach 1×10⁻⁶. -4 S / cm or higher.
[0017] (2) This invention employs needleless electrospinning technology, overcoming the problem of low efficiency in traditional needled electrospinning. The spinning efficiency is 20 times that of traditional needled electrospinning. It enables continuous and large-scale production of composite fiber skeletons, providing a feasible path for the industrial application of solid electrolytes.
[0018] (3) The composite fiber skeleton in the composite solid electrolyte of the present invention provides excellent mechanical strength and effectively inhibits the growth of lithium dendrites. The in-situ polymer matrix has good flexibility and interfacial wettability to the electrode, reducing interfacial impedance. Furthermore, since the inorganic nanofiller is embedded in the composite fiber skeleton rather than simply mixed, there is no macroscopic interface between the inorganic nanofiller and the polymer matrix as in traditional composite electrolytes, resulting in a smoother ion transport path and avoiding local stress concentration caused by the agglomeration of inorganic nanofiller.
[0019] (4) By optimizing the proportions of each component and process parameters, the composite solid electrolyte prepared by this invention exhibits high ionic conductivity (≥1×10⁻⁶) at room temperature. -4 With its high S / cm, wide electrochemical window (>4.5V), and good thermal stability, it exhibits excellent cycle performance and rate performance when used in the assembly of lithium-ion batteries.
[0020] The present invention will now be described in further detail with reference to the accompanying drawings. Attached Figure Description
[0021] Figure 1 Here is a scanning electron microscope (SEM) image of the composite fiber skeleton prepared in Example 1 of this invention; Figure 2 This is a SEM image of the composite solid electrolyte prepared in Example 1 of the present invention; Figure 3 This is a schematic diagram of the composite solid electrolyte prepared in Example 1 of the present invention; Figure 4 This is a graph showing the cycle performance of the lithium-ion battery assembled in Example 1 of the present invention at room temperature; Figure 5 This is a SEM image of the lithium metal anode surface of the battery assembled in Example 1 of the present invention after cycling at room temperature. Detailed Implementation
[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] This invention provides a method for preparing a composite solid electrolyte based on needle-free electrospinning technology, comprising the following steps: S1. Dissolve the inorganic nanofiller and polymer matrix in a solvent and stir until homogeneous to obtain a spinning precursor solution.
[0024] Specifically, the inorganic nanofiller has a mass percentage of 3-8% in the spinning precursor solution, preferably 5%; the polymer matrix has a mass percentage of 8-12% in the spinning precursor solution, preferably 10%.
[0025] Optionally, the inorganic nanofiller may be at least one of lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanium oxide (LLTO), and titanium dioxide (TiO2); the polymer matrix may be at least one of polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), and polyimide (PI); and the solvent may be one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), deionized water, or ethanol.
[0026] S2. The spinning precursor liquid is spun using a needleless electrospinning device to obtain a composite fiber skeleton with a three-dimensional network structure.
[0027] Specifically, the process parameters for needleless electrospinning equipment are: spinning voltage of 30-80kV, receiving distance of 150-250mm, spinning ambient temperature of 20-40℃, and relative humidity of 30-50%.
[0028] S3. Provide a polymer precursor solution, the polymer precursor solution comprising a polymer monomer, a crosslinking agent, an additive, and a lithium salt.
[0029] Specifically, the mass ratio of polymeric monomer, crosslinking agent and additive is (2-5):(1-3):(0.5-1.5), and the lithium salt concentration is 1-3M; preferably, the mass ratio of polymeric monomer, crosslinking agent and additive is 3:2:1.
[0030] Optionally, the polymerizing monomer may be at least one selected from 2,2,3,4,4,4-hexafluorobutyl methacrylate (HFA), succinic anionyl nitrile (SN), methyl methacrylate (MMA), acrylonitrile (AN), and 1,3-dioxolane (DOL); the crosslinking agent may be at least one selected from polyethylene glycol diacrylate (PEGDA), pentaerythritol tetraacrylate (PETEA), trimethylolpropane triacrylate (TMPTA), and polyethylene glycol dimethacrylate (PEGDMA); the additives may also be selected from... It is at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), lithium difluorooxalate borate (LiDFOB), and succinate (SN); the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)amino (LiFTFSI), lithium trifluoromethanesulfonyl)imide (LiPTFSI), lithium difluorooxalate borate (LiDFOB), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4).
[0031] S4. Add a thermal initiator to the polymer precursor solution, and immerse the composite fiber skeleton in the mixed solution of the polymer precursor solution and the thermal initiator. Under heating conditions, the impregnated composite fiber skeleton undergoes an in-situ polymerization reaction, and after curing, a composite solid electrolyte is obtained.
[0032] Specifically, the thermal initiator is azobisisobutyronitrile (AIBN); the heating temperature of the in-situ polymerization reaction is 50–80°C, and the reaction time is 1–4 h.
[0033] Preferably, the method for preparing the mixed solution of the polymer precursor solution and the thermal initiator includes: The monomer, crosslinking agent, first portion of lithium salt and thermal initiator are mixed to obtain component A; the additive and second portion of lithium salt are mixed to obtain component B; component A and component B are mixed to obtain a mixed solution. A mixed solution of polymer precursor solution and thermal initiator was prepared using a two-component (A and B) formulation strategy, with the components mixed immediately before use. Component A (initiator and crosslinking component) contains polymer monomers, crosslinking agents, lithium salts, and thermal initiators, while component B (plasticizer and conduction component) contains additives (plasticizers) and lithium salts. This formulation method ensures that, on the one hand, the thermal initiator and monomers are pre-mixed in component A, avoiding gelation of the thermal initiator due to competitive dissolution or pre-reaction in a system containing a high proportion of plasticizer solvent, thus significantly extending the pot life of the precursor solution. On the other hand, the thermal initiator is precisely and uniformly dispersed in the polymer monomer / crosslinking agent system of component A, improving the degree of crosslinking and reaction uniformity of subsequent in-situ thermal polymerization. Simultaneously, the independent formulation of components A and B reduces the system viscosity, significantly improving the microscopic wetting rate and depth of the polymer precursor solution into the pores of the nanofiber framework, ensuring sufficient filling of the fiber pores.
[0034] In this invention, needleless electrospinning technology is used to prepare composite fiber skeleton, which has unique mechanistic advantages for the uniform dispersion of inorganic nanofillers, specifically in the following aspects: (1) Under the action of a high voltage electric field, needleless electrospinning simultaneously forms a large number of Taylor cones on the solution surface and initiates multiple jets. Its Taylor cone density is much higher than that of traditional needled electrospinning. Each jet undergoes severe fluid shearing and rapid stretching during the stretching and fiber formation process. The high shear stress generated by this process effectively disperses the weak aggregates of inorganic nanofillers in the spinning precursor liquid, so that the inorganic nanofiller particles achieve uniform dispersion at the nanoscale in the polymer matrix; (2) The fiber skeleton constructed by needleless electrospinning has a three-dimensional network structure. The inorganic nanofillers are uniformly embedded in the interior and surface of each fiber. Adjacent fibers form a continuous filler network through point contact, thereby providing a long-range continuous and rapid transport path for lithium ions, significantly improving the ionic conductivity of the composite electrolyte.
[0035] The preparation process and performance of the composite solid electrolyte of the present invention are illustrated below through specific embodiments and comparative examples.
[0036] Example 1: This embodiment provides a method for preparing a composite solid electrolyte based on needle-free electrospinning technology. The specific process is as follows: 5 wt% LLTO and 10 wt% PAN were added to 25 mL of NMP solvent and stirred for 12 hours to obtain a uniform spinning precursor solution. Spinning was carried out using a needleless electrospinning device with the following process parameters: voltage 60 kV, receiving distance 200 mm, temperature 25 °C, and humidity 40%. A composite fiber skeleton with a thickness of about 30 µm was collected.
[0037] MMA, PEGDA, and VC were mixed in a mass ratio of 1:1:1, and 1M LiTFSI was added and stirred until completely dissolved to obtain a polymer precursor solution. Then, 0.5 wt% AIBN was added and stirred until completely dissolved to obtain polymer precursor solution A. Subsequently, 1M LiTFSI was added to SN and stirred until completely dissolved to obtain polymer precursor solution B. Finally, the above composite fiber skeleton was immersed in the polymer precursor solution (A:B=3:7) for 30 minutes, removed and placed in a vacuum oven, and heated at 60°C for 2 hours to obtain a composite solid electrolyte.
[0038] Figure 1 The image shown is an SEM image of the composite fiber skeleton prepared in this embodiment; as can be seen from the image, the prepared composite fiber skeleton has a uniform three-dimensional network structure and uniform fiber diameter.
[0039] Figure 2 and 3 The figures show SEM images and structural schematic diagrams of the composite solid electrolyte prepared in this embodiment. As can be seen from the figures, the polymer precursor was successfully polymerized in situ and filled into the pores of the composite fiber skeleton, forming a dense and continuous composite solid electrolyte membrane.
[0040] The composite solid electrolyte of this embodiment was assembled with a lithium iron phosphate cathode and a lithium metal anode into a coin cell, and its cycle performance was tested at room temperature. The results are as follows: Figure 4 As shown in the figure, the test results show that after 100 cycles at a discharge rate of 0.5C, the capacity retention rate is as high as 96%, demonstrating excellent cycle stability.
[0041] Furthermore, SEM tests were performed on the surface of the lithium metal anode of the battery after cycling at room temperature, and the results are as follows: Figure 5 As shown in the figure, after 100 cycles at a discharge rate of 0.5C, no lithium dendrites were generated on the surface of the lithium metal anode, indicating that the composite solid electrolyte of the present invention effectively suppressed the growth of lithium dendrites.
[0042] Example 2: This embodiment investigates the effect of inorganic nanofiller content on the performance of solid electrolytes.
[0043] PAN (10 wt%) and different mass fractions (1 wt%, 3 wt%, 5 wt%, 8 wt%, and 12 wt%) of LLTO were added to 25 mL of NMP solvent and stirred to form a homogeneous spinning precursor solution. Electrospinning was performed using an electrospinning apparatus under conditions of 60 kV, a receiving distance of 200 mm, a temperature of 25 °C, and a humidity of 40% to obtain a composite fiber skeleton. The composite fiber skeleton was immersed in a precursor solution composed of MMA, PEGDA, VC (mass ratio 3:2:1), and 0.5% AIBN (thermal initiator). After removal, it was heated at 60 °C for 2 hours to polymerize, yielding a composite solid electrolyte.
[0044] The results showed that when the LLTO content was 3 wt%, the ionic conductivity was 5.2 × 10⁻⁶. -5 S / cm; When the LLTO content is 5wt%, LLTO is evenly distributed in the fiber, forming a good ion conduction network, and the ion conductivity is increased to 1.3×10. - 4 S / cm; When the LLTO content increased to 8 wt%, a small amount of LLTO agglomerates appeared on the fiber surface. Although a small amount of agglomerates appeared on the fiber surface and the flexibility slightly decreased, the electrical conductivity remained at 1.1×10. -4 The high S / cm level ensures that the overall performance still meets the standards. However, when the LLTO content is below 3 wt% (e.g., 1 wt%), the insufficient concentration of inorganic nanofillers prevents the formation of a continuous and effective high conductivity pathway, resulting in limited improvement in conductivity and making the performance unfeasible. When the LLTO content exceeds 8 wt% (e.g., reaching 12 wt%), the LLTO particles will severely agglomerate, which will not only drastically damage the mechanical flexibility and integrity of the electrospinning skeleton, but also block ion transport channels, leading to performance failure.
[0045] Example 3: This example investigates the effect of the ratio of MMA, PEGDA, and VC in the polymer precursor solution.
[0046] The preparation process of the composite fiber skeleton in this embodiment is the same as in Example 1 above; the ratio of MMA, PEGDA and VC in the polymer precursor solution is changed to (6:1:1), (4:1:1), (3:1:1), (2:1:1) and (1:1:4) respectively, and impregnation and in-situ polymerization are carried out according to the method of Example 1 above.
[0047] The results showed that when the MMA ratio was too high (e.g., MMA:PEGDA:VC = 6:1:1), the polymer matrix was too soft, and the mechanical strength of the composite solid electrolyte membrane decreased. When the VC ratio was too high (e.g., MMA:PEGDA:VC = 1:1:4), the polymerization rate was too fast, easily leading to localized inhomogeneities. When MMA, PEGDA, and VC were mixed in a mass ratio of 2:1:1, and 1M LiTFSI was added and stirred until completely dissolved, followed by the addition of 0.5 wt% AIBN and stirring until completely dissolved, polymer precursor solution A was obtained. Then, 1M LiTFSI was added to the SN and stirred until completely dissolved, yielding polymer precursor solution B. Finally, polymer precursor solutions A and B were mixed in a ratio of A:B = 3:7, resulting in a solid electrolyte that exhibited both good flexibility and mechanical strength, and had the lowest interfacial impedance with the electrode.
[0048] Example 4: This embodiment investigates the effect of in-situ polymerization temperature. The preparation process of the composite solid electrolyte in this embodiment is roughly the same as that in Example 1 above. The difference is that in this embodiment, the polymerization reaction is carried out at 20℃, 50℃, 60℃, 80℃ and 120℃ for 2 hours respectively during the heating polymerization process.
[0049] The invention found that when the heating polymerization temperature is too low (e.g., 20°C), the polymerization is incomplete, and some liquid remains, resulting in poor electrolyte membrane formability. When the heating polymerization temperature is too high (e.g., 120°C), the polymerization rate is too fast, which may generate bubbles, resulting in an uneven surface of the composite solid electrolyte membrane. The polymerization reaction is complete at 60°C, resulting in a uniform and dense membrane structure and the best overall performance.
[0050] Example 5: This embodiment provides a method for preparing a composite solid electrolyte based on needle-free electrospinning technology. The specific process is as follows: 5 wt% LLZTO and 10 wt% PVDF were added to 25 mL of DMF solvent and stirred for 12 hours to obtain a homogeneous spinning precursor solution. Electrospinning was performed using an electrospinning device with the following process parameters: voltage 60 kV, receiving distance 200 mm, temperature 25 °C, and humidity 40%. A composite fiber skeleton with a thickness of approximately 30 µm was collected.
[0051] SN, PEGDMA, and VC were mixed in a mass ratio of 1:1:1, and 1M LiTFSI was added and stirred until completely dissolved to obtain a polymer precursor solution. Then, 0.5 wt% AIBN was added and stirred until completely dissolved to obtain polymer precursor solution A. Subsequently, 1M LiTFSI was added to SN and stirred until completely dissolved to obtain polymer precursor solution B. Finally, the above composite fiber skeleton was immersed in the polymer precursor solution (A:B=4:7) for 30 minutes, removed and placed in a vacuum oven, and heated at 65°C for 2 hours to obtain a composite solid electrolyte.
[0052] Example 6: This embodiment investigates the effect of the ratio of SN, PEGDMA, and VC in the polymer precursor solution. The preparation process of the composite solid electrolyte in this embodiment is roughly the same as that in Example 5 above, except that the ratios of SN, PEGDMA, and VC in the polymer precursor solution in this embodiment are (7:1:1), (4:1:1), (3:1:1), (2:1:1), and (1:1:4), respectively.
[0053] The results showed that when the SN ratio was too high (e.g., 7:1:1), the polymer matrix was too soft, and the mechanical strength of the composite solid electrolyte membrane decreased. When the VC ratio was too high (e.g., 1:1:4), the polymerization rate was too fast, which easily led to local inhomogeneity. When the ratio of SN, PEGDMA, and VC was mixed at a mass ratio of 2:1:1, 1M LiTFSI was added and stirred until completely dissolved, followed by the addition of 0.5 wt% AIBN and stirring until completely dissolved to obtain polymer precursor solution A, then 1M LiTFSI was added to SN and stirred until completely dissolved to obtain polymer precursor solution B. Finally, when polymer precursor solutions A and B were mixed at a ratio of A:B=4:7, the resulting composite solid electrolyte exhibited both good flexibility and mechanical strength, and had the lowest interfacial impedance with the electrode.
[0054] Example 7: This embodiment investigates the effect of in-situ polymerization temperature. The preparation process of the composite solid electrolyte in this embodiment is roughly the same as that in Example 5 above. The difference is that in this embodiment, the polymerization reaction is carried out at 25°C, 55°C, 65°C, 80°C and 120°C for 2 hours during the heating polymerization process.
[0055] The results showed that polymerization was incomplete at 25℃, with some liquid remaining, resulting in poor electrolyte membrane formability; polymerization rate was too fast at 120℃, which may generate bubbles and make the surface of the composite solid electrolyte membrane uneven; polymerization reaction was complete at 65℃, resulting in a uniform and dense membrane structure and the best overall performance.
[0056] Comparative Example 1: This comparative example uses a traditional blending and casting method to prepare a composite solid electrolyte. The polymer precursor solution from Example 1 above (mixing MMA, PEGDA, and VC in a mass ratio of 1:1:1, adding 1M LiTFSI and stirring until completely dissolved, then adding 0.5 wt% AIBN and stirring until completely dissolved to obtain polymer precursor solution A, then adding 1M LiTFSI and stirring until completely dissolved to obtain polymer precursor solution B, and finally mixing polymer precursor solutions A and B in a ratio of A:B=3:7; and containing 14 wt% LLTO) was directly cast into a polytetrafluoroethylene mold and polymerized at 60°C for 2 hours to prepare a composite solid electrolyte membrane.
[0057] The composite solid electrolyte membrane prepared in this comparative example has a uniform structure, but the inorganic nanofiller LLTO is unevenly distributed in the membrane, resulting in agglomeration; moreover, its room temperature ionic conductivity is only 4.5 × 10⁻⁶. -5 S / cm, much lower than 1.3 × 10⁻⁶ in Example 1. - 4 S / cm.
[0058] Comparative Example 2: In this comparative example, the spinning precursor liquid in Example 1 above was spun using a conventional single-needle electrospinning device.
[0059] The results show that the traditional needle-type electrospinning method has extremely low efficiency, with a yield that is only 1 / 20 of the needleless electrospinning equipment of this invention. Furthermore, the prepared fiber membrane has a small area and uneven thickness, and the composite solid electrolyte prepared by it has poor reproducibility.
[0060] Comparative Example 3: In this comparative example, LLTO was not added to the spinning precursor solution, and only 10% PAN was used for spinning. The other steps were the same as in Example 1.
[0061] The results show that the ionic conductivity of the composite solid electrolyte obtained in this comparative example is only 8.2 × 10⁻⁶ at 25 °C. -6 The S / cm ratio indicates that the addition of LLTO inorganic nanofiller is crucial for constructing an efficient ion transport network.
[0062] Comparative Example 4: In this comparative example, the polymer precursor solution from Example 5 above (SN, PEGDMA, and VC were mixed in a mass ratio of 1:1:1, 1M LiTFSI was added and stirred until completely dissolved, then 0.5 wt% AIBN was added and stirred until completely dissolved to obtain polymer precursor solution A, then 1M LiTFSI was added and stirred until completely dissolved to obtain polymer precursor solution B, and finally polymer precursor solutions A and B were mixed in a ratio of A:B=4:7; and contained 14 wt% LLZTO) was directly cast into a polytetrafluoroethylene mold and polymerized at 65°C for 2 hours to prepare a composite solid electrolyte membrane.
[0063] The composite solid electrolyte membrane prepared in this comparative example has a uniform structure, but the inorganic nanofiller LLZTO is unevenly distributed in the membrane, resulting in agglomeration; moreover, its room temperature ionic conductivity is only 4.3 × 10⁻⁶. -5 S / cm, much lower than 1.4 × 10 in Example 5. -4 S / cm.
[0064] Comparative Example 5: In this comparative example, the spinning precursor liquid in Example 5 above was spun using a conventional single-needle electrospinning device.
[0065] The results show that the traditional needle-type electrospinning method has extremely low efficiency, with a yield that is only 1 / 20 of the needleless electrospinning equipment of this invention. Furthermore, the prepared fiber membrane has a small area and uneven thickness, and the composite solid electrolyte prepared by it has poor reproducibility.
[0066] Comparative Example 6: In this comparative example, LLZTO was not added to the spinning precursor solution, and only 10% PVDF was used for spinning. The other steps were the same as in Example 5.
[0067] The results show that the composite solid electrolyte obtained in this comparative example has an ionic conductivity of only 7.8 × 10⁻⁶ at 25 °C. -6 The S / cm ratio indicates that the addition of LLZTO inorganic nanofiller is crucial for constructing an efficient ion transport network.
[0068] The above examples are merely illustrative of the present invention and do not constitute a limitation on the scope of protection of the present invention. All designs that are the same as or similar to the present invention are within the scope of protection of the present invention.
Claims
1. A method for preparing composite solid electrolytes based on needle-free electrospinning technology, characterized in that, Includes the following steps: S1. Dissolve the inorganic nanofiller and polymer matrix in a solvent and stir until homogeneous to obtain a spinning precursor solution; S2. The spinning precursor liquid is spun using a needleless electrospinning device, and a composite fiber skeleton with a three-dimensional network structure is collected. S3. Provide a polymer precursor solution, the polymer precursor solution comprising a polymer monomer, a crosslinking agent, an additive, and a lithium salt; S4. Add a thermal initiator to the polymer precursor solution, and immerse the composite fiber skeleton in the mixed solution of the polymer precursor solution and the thermal initiator. Under heating conditions, the impregnated composite fiber skeleton undergoes an in-situ polymerization reaction, and after curing, a composite solid electrolyte is obtained.
2. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that, In S1, the inorganic nanofiller has a mass percentage of 3-8% in the spinning precursor solution, and the polymer matrix has a mass percentage of 8-12% in the spinning precursor solution.
3. The method for preparing the composite solid electrolyte as described in claim 1 or 2, characterized in that, In S1, the inorganic nanofiller is at least one of lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, and titanium dioxide; the polymer matrix is at least one of polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polymethyl methacrylate, polyvinyl alcohol, and polyimide; and the solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, deionized water, or ethanol.
4. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that, In S2, the process parameters of the needleless electrospinning equipment are: spinning voltage of 30-80kV, receiving distance of 150-250mm, spinning ambient temperature of 20-40℃, and relative humidity of 30-50%.
5. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that, In S3, the mass ratio of polymeric monomer, crosslinking agent and additive is (2-5):(1-3):(0.5-1.5), and the lithium salt concentration is 1-3M.
6. The method for preparing the composite solid electrolyte as described in claim 1 or 5, characterized in that, In S3, the polymerizing monomer is at least one of 2,2,3,4,4,4-hexafluorobutyl methacrylate, succinic anion, methyl methacrylate, acrylonitrile, and 1,3-dioxolane; the crosslinking agent is at least one of polyethylene glycol diacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, and polyethylene glycol dimethacrylate; the additive is at least one of vinylene carbonate, fluoroethylene carbonate, lithium difluorooxalate borate, and succinic anion; and the lithium salt is at least one of LiTFSI, LiFSI, LiFTFSI, LiPTFSI, LiDFOB, LiPF6, and LiBF4.
7. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that, The method for preparing the mixed solution of the polymer precursor solution and the thermal initiator includes: The polymer monomer, crosslinking agent, first-part lithium salt and thermal initiator are mixed to obtain component A; The additive and the second lithium salt were mixed to obtain component B; The mixture of component A and component B yields a mixed solution.
8. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that, In S4, the thermal initiator is azobisisobutyronitrile; the heating temperature for the in-situ polymerization reaction is 50–80°C, and the reaction time is 1–4 h.
9. A composite solid electrolyte, characterized in that, The composite solid electrolyte is prepared by the method according to any one of claims 1-8, wherein the composite solid electrolyte comprises a composite fiber skeleton having a three-dimensional network structure and an in-situ polymer matrix filling the pores of the composite fiber skeleton.
10. The composite solid electrolyte as described in claim 9, characterized in that, The composite solid electrolyte has a thickness of 20–60 µm and an ionic conductivity of 1 × 10⁻⁶ at 25 °C. -4 S / cm or higher.
